2012
DOI: 10.1179/1743284711y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Changes of γ′ precipitate characteristics in damaged superalloy IN738LC during different stages of rejuvenation heat treatment cycles

Abstract: The present study investigates the evolution of c9 precipitate microstructure in a creep damaged IN738LC superalloy during different stages of rejuvenation heat treatment cycles. Dissolution of coarsened c9 precipitates in the creep damaged alloy occurred during different solution treatments. The precipitates that did not dissolve completely during solution treatment and those formed during subsequent cooling were considered to be as remnant and cooling precipitates respectively. It was found that higher solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…– approximately 24,000 h) recommended by the manufacturer. The huge cost of replacement components has driven the development of refurbishing processes to recover the microstructure and properties of the blades [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…– approximately 24,000 h) recommended by the manufacturer. The huge cost of replacement components has driven the development of refurbishing processes to recover the microstructure and properties of the blades [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…By studying the creep behaviour of Nimonic 105, Girdwood and Evans [8] found that completed re-solution heat treatment could heal the creep damaged microstructure. Hosseini et al [9] compared the original, damaged and re-heat treatment of the IN738LC alloy, and found that coarsening γ′ and carbides in the MC type transforming area could be dissolved back into the matrix. However, the main concern of these studies is the evolution of damaged microstructure during heat treatment and lack of research on the effect of heat treatment parameters, especially the cooling rate.…”
Section: Introductionmentioning
confidence: 99%